Novel obverse structural solar cell - TANG ANMIN (2014)
The utility model discloses a novel obverse structural solar cell. The solar cell comprises a positive electrode, a passivation layer, a P-N junction, a P-type substrate, A plurality of openings are arranged in the passivation layer. An ITO thin layer is deposited on the passivation layer. The obverse contact resistors of the solar cell can be decreased, the fill factor can be raised, the short circuit current can be increased and the obverse silver paste dosage can be decreased.